2018
DOI: 10.1007/s00261-018-1658-1
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous colorectal cancer using CT colonography vs. other means: a systematic review and meta-analysis

Abstract: The prevalence of synchronous CRC was about 4-6%. The introduction of CTC is associated with a significant increase of the prevalence of synchronous CRCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 65 publications
0
12
0
3
Order By: Relevance
“…Moreover, stent of an obstructing cancer is yet to be recommended as a standard treatment, and colonoscopy may be dangerous through a colonic stent even though feasible[ 26 ]. The colon may also be satisfactorily evaluated with imaging modalities (virtual coloscopy, CT-colonography, magnetic resonance colonography, intra-operative or post-operative coloscopy)[ 1 , 15 , 20 , 27 ]. Thus, every reasonable effort should be made to evaluate the entire colon before planning definitive intervention[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, stent of an obstructing cancer is yet to be recommended as a standard treatment, and colonoscopy may be dangerous through a colonic stent even though feasible[ 26 ]. The colon may also be satisfactorily evaluated with imaging modalities (virtual coloscopy, CT-colonography, magnetic resonance colonography, intra-operative or post-operative coloscopy)[ 1 , 15 , 20 , 27 ]. Thus, every reasonable effort should be made to evaluate the entire colon before planning definitive intervention[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, houve uma particularidade no caso, uma vez que os tumores acometeram o mesmo segmento. 10 No caso descrito, houve a realização completa da colonoscopia, porém não houve a detecção do CCRs, sendo apenas identificado no pós-operatório. Chin, Kuo e Chiang 8 afirmam que o diagnóstico préoperatório preciso de CCRs é fundamental para definir o tipo e a extensão dos tratamentos cirúrgicos.…”
Section: Discussionunclassified
“…Essas lesões adicionais precisam ser distintamente separadas por pelo menos 4cm de distância do CCR índice e não podem constar disseminação de submucosa ou ser uma lesão satélite do CCR índice. 8,10 O CCR geralmente é assintomático, por isso é importante que medidas preventivas sejam implantadas como forma de se detectar a doença em estágio inicial, proporcionando ao paciente mais chances de obter a cura. Além disso, deve-se atentar aos sinais e sintomas de alerta que fazem parte do quadro clínico da doença, como mudanças nos hábitos intestinais, dor abdominal, sangue oculto e alterações nas fezes.…”
unclassified
“…Incomplete colonoscopy for neoplastic lesions -CTC Almost all cases of incomplete optical colonoscopy due to occlusive cancer can be examined successfully with CTC [24,25] and one study showed that preoperative CTC, after an incomplete optical colonoscopy, contributed to a change in the surgical plan in 14 of 65 patients (21.5%). Up to 35.1% (range 22.3 % -45.4 %) of synchronous neoplasms occur in one or more different segments from the distal tumor so their detection will change management in a significant number of patients [26].…”
Section: Completion Of a Previously Incomplete Colonoscopymentioning
confidence: 99%